Website-Based Retail Sales Monitoring System at Purbaratu Market Cooperative, Tasikmalaya City - Cahyadi, Cepi; Jaelani, Rusani; Arfian, Andi (Internet of Things and Artificial Intelligence Journal, 2024)
Purbaratu Market is a gathering place for traders and buyers who always have buying and selling transactions every day. This market has a cooperative to monitor everything in the market, but the retail sales transaction process system in the current cooperative is still traditional in the buying and selling of merchandise, therefore, transactions need to be monitored carefully and quickly to find out transactions consisting of various types of goods, so it requires accuracy in recording the type and number of products sold, Based on the description of existing problems, an increase in services in the field of computerization is carried out. That is, this traditional system will be developed into a digital system in the form of a monitoring system for Retail Sales of the Purbaratu market cooperative. This technology is made using PHP and MySQL databases. The purpose of planning this application is to provide convenience in the process of transactions and processing retail sales data in the Purbaratu market cooperative.